Individualization of land rights and gender-differentiated inheritance in matrilineal Sumatra: efficiency and equity implications - Quisumbing, Agnes R.; Otsuka, Keijiro (International Food Policy Research Institute, 1998)
This paper examines the equity implications of the evolution of land rights from communal land tenure to individualization in customary land areas in Western Sumatra. This brief sets forth policy implications: Preference for sons in the inheritance of agroforestry area in the Low Region may be explained by the intensive use of male labor in rubber production; in contrast, both paddy cultivation and cinnamon cultivation in the Middle Region use both male and female family labor relatively equally. The inheritance system seems to be evolving from a strictly matrilineal system to a more egalitarian system in which sons and daughters inherit the type of land which is more intensive in their own work effort. That is, the newly-emerging customary land tenure institutions, by allowing for inheritance consistent with comparative advantage and work effort, seem to have built-in incentives for men and women. The persistent gender gap in schooling, however, needs to be addressed. Even if daughters continue to have independent land rights, lower levels of education make them less likely to benefit from nonagricultural income earning opportunities...Investing in the education of both sons and daughters would thus be part of a long-term solution to rural poverty and environmental sustainability in these areas.